TRANSFORMING LEARNING EXPERIENCES IN ART AND DESIGN APPRECIATION: A RESEARCH ON E-LEARNING DESIGN AND DEVELOPMENT - Devanny Gumulya (Universitas Terbuka, 2023)
The paper focuses on the design and development of an e-learning course in art and design appreciation. Using the ADDIE model, the study explores the integration of the See Think Wonder approach in the e-learning context. The research aims to enhance learners' engagement, understanding, and appreciation of art and design. The study consists of analysis, design, development, implementation, and evaluation of art and design appreciation e-learning. The findings indicate that the See Think Wonder approach positively impacts the e-learning environment by increasing learner engagement, critical thinking skills, and emotional connection to artworks. The approach facilitates active participation, critical discussions, and improved observation and interpretation of artworks. The e-learning platform offers flexibility and accessibility, enabling learners to study at their own pace. Multimedia elements and interactive activities enhance the learning experience. Evaluation results support the effectiveness of the course, with learners recognizing the value of the See Think Wonder approach in enhancing art and design appreciation. It improves their confidence in analyzing artworks and deepens their understanding of artistic elements and principles. The research contributes to the field of art and design education by highlighting the potential of e-learning in transforming learning experiences. It provides insights for educators and instructional designers seeking to enhance art and design education through digital platforms.